2018
DOI: 10.1148/rg.2018170048
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and CT Features of Viral Pneumonia

Abstract: Viruses are the most common causes of respiratory infection. The imaging findings of viral pneumonia are diverse and overlap with those of other nonviral infectious and inflammatory conditions. However, identification of the underlying viral pathogens may not always be easy. There are a number of indicators for identifying viral pathogens on the basis of imaging patterns, which are associated with the pathogenesis of viral infections. Viruses in the same viral family share a similar pathogenesis of pneumonia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
511
4
17

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 624 publications
(595 citation statements)
references
References 86 publications
41
511
4
17
Order By: Relevance
“…In the chest HRCT manifestations patients in this study, patchy GGO and consolidation were common features. Similar manifestations were also present in severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) infections, as shown in previous studies [8][9] . In this study, the lesions of patients were mainly located in the lower lobe of the right lung.…”
Section: Covid-19 Infection and Distinguished Imaging Signs Between Psupporting
confidence: 82%
“…In the chest HRCT manifestations patients in this study, patchy GGO and consolidation were common features. Similar manifestations were also present in severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS) infections, as shown in previous studies [8][9] . In this study, the lesions of patients were mainly located in the lower lobe of the right lung.…”
Section: Covid-19 Infection and Distinguished Imaging Signs Between Psupporting
confidence: 82%
“…In a recent review for radiologic imaging of viral agents that may cause pneumonia, the general radiologic findings of hMPV infections were followed as bilateral centrilobular nodules, GGO, and multilobar infiltrations; however, there was no information about nodular consolidation. In addition, they noted that the radiologic findings of hMPV infections were most commonly reported in patients with hematologic malignancy, but there were limited data on immunocompetent patients . Similar radiologic findings in hMPV infection among immunocompromised patients have been reported in different studies .…”
Section: Discussionsupporting
confidence: 81%
“…Radiologic findings of hMPV infection have not been reported to be different from other viral pathogens in studies with high sample sizes; however, it has been reported that studies including radiologic findings of hMPV infections were commonly done among immunocompromised hosts …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it was difficult to distinguish if the consolidation was associated with COVID-19 pneumonia, since the consolidation and pleural effusion were also common in pure RSV infection. 27 The contact history and clinical symptoms of fever or cough may be helpful for the surveillance.…”
Section: Discussionmentioning
confidence: 99%